Formulasi Salep Ekstrak Etanol Daun Tapak Kuda (Ipomoea pes-caprae) Dan Uji Efektivitasnya Terhadap Luka Terbuka Pada Punggung Kelinci - Muthalib, Eka Mulya; Fatimawali, Fatimawali; Edy, Hosea Jaya (PHARMACON, 2013)
ABSTRACTPalm horse weevil contains medicinal properties that are useful in the process of woundhealing. The purpose of this study is to to examine formulate an ointment of palm horse(Ipomoea pes-caprae (L) Sweet) weevil extract and to test the ointment to heal open woundon the skin of rabbits. This study is experimental descriptive in the laboratory. Palm horseweevil extracts used in the manufactured of ointment formulation 10%, 15 % and 20 %. Theresults showed that the palm horse weevil formulation meets the ointment test requirementaccording, making ointment formulation using cassava tuber extract used as 5 rabbits.Divided into 5 treatment gropus, namely, test the ointment treatment group, negative controlgroup (basic ointment) and positive control group (chloramphenicol ointment). Observed thehealing effects for 7 days. The results showed that from day-1 to day-7 observations burnssuffered diminution in diameter. It was concluded that concentration of 10 % cassava extractontment has healing effect and increasing the concentration of 15 % and 20 % containedshowed more effective and speed up the healing process.Keywords : Extract leaf palm horse , ointment, wound healing, rabbit.